Effect of oxygen on the expression of renin-angiotensin system components in a human trophoblast cell line - Delforce, Sarah J.; Wang, Yu; Van-Aalst, Meg E.; Corbisier de Meaultsart, Celine; Morris, Brian J.; Broughton Pipkin, Fiona; Roberts, Claire T.; Lumbers, Eugenie R.; Pringle, Kirsty G. (Elsevier, 2016)
During the first trimester, normal placental development occurs in a low oxygen environment that is known to stimulate angiogenesis via upregulation of vascular endothelial growth factor (VEGF). Expression of the placental renin-angiotensin system (RAS) is highest in early pregnancy. While the RAS and oxygen both stimulate angiogenesis, how they interact within the placenta is unknown. We postulated that low oxygen increases expression of the proangiogenic RAS pathway and that this is associated with increased VEGF in a first trimester human trophoblast cell line (HTR-8/SVneo). HTR-8/SVneo cells were cultured in one of three oxygen tensions (1%, 5% and 20%). RAS and VEGF mRNA expression were determined by qPCR. Prorenin, angiotensin converting enzyme (ACE) and VEGF protein levels in the supernatant, as well as prorenin and ACE in cell lysates, were measured using ELISAs. Low oxygen significantly increased the expression of both angiotensin II type 1 receptor (AGTR1) and VEGF (both P < 0.05). There was a positive correlation between AGTR1 and VEGF expression at low oxygen (r = 0.64, P < 0.005). Corresponding increases in VEGF protein were observed with low oxygen (P < 0.05). Despite no change in ACE1 mRNA expression, ACE levels in the supernatant increased with low oxygen (1% and 5%, P < 0.05). Expression of other RAS components did not change. Low oxygen increased AGTR1 and VEGF expression, as well as ACE and VEGF protein levels, suggesting that the proangiogenic RAS pathway is activated. This highlights a potential role for the placental RAS in mediating the proangiogenic effects of low oxygen in placental development.